Rice flakes produced from commercial wild rice: Chemical compositions, vitamin B compounds, mineral and trace element contents and their dietary intake evaluation - Sumczynski, Daniela; Koubová, Eva; Šenkárová, Lenka; Orsavová, Jana (Food chemistry, 2018)
Non-traditional wild rice flakes were analysed for chemical composition, vitamin B compounds, α-tocopherol, mineral and trace elements. Dietary intakes of vitamins, minerals and trace elements were evaluated using FAO/WHO and Institute of Medicine regulations. Wild rice flakes proved to be significant contributors of pyridoxine, pantothenic and folic acids, niacin, thiamine, chromium, magnesium, manganese, phosphorus, zinc, copper, molybdenum and iron to essential dietary intakes values. Toxic dietary intake values for aluminium, cadmium, tin and mercury were less than 33%, which complies the limits for adults set by FAO/WHO for toxic elements intake related to the body weight of 65 kg for females and 80 kg for males taking 100 g of flakes as a portion. However, concentrations of Hg reaching between 3.67 and 12.20 µg/100 g in flakes exceeded the average Hg value of 0.27-1.90 μg/100 g in cereals consumed in the EU. It has to be respected in the future.
Keywords: Chromatography, High Pressure Liquid; Metals, Heavy; alfa-tokoferol; Daily intake; Humans; Diet; rýže (rod); Female; dospělí; stopové prvky; lidé; vitamin B komplex; Wild rice flakes; Minerals; Mineral and trace elements; Adult; těžké kovy; ženské pohlaví; Oryza; Vitamin; Male; Vitamin B Complex; dieta; Trace Elements; Zizania aquatica L.; alpha-Tocopherol; výživová politika; mužské pohlaví; hmotnostní spektrometrie; minerály; Nutrition Policy; vysokoúčinná kapalinová chromatografie; Mass Spectrometry